INDONESIAN ISLAMIC MOVEMENT OF WOMEN: A STUDY OF FATAYAT MUSLIMAT NU (1938-2013) - Hamidah Hamidah (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2016)
Abstract: The purpose of this article is to examine the dynamics of Indonesian Muslim women's movement of a socio-historical study of the Moslem-Fatayat NU during the period 1938-2013. The socio-historical, Indonesian Islamic women's movement can exist not only from tahrirul mar'ah movement but also the influence of the feminist movement that developed in the Western world. The development of Moslem-Fatayat plays a strategic role in social transformation efforts. Transformation through a process of awareness that ran in "evolutionary manner" rather than radical which prescribes to actualization of classical islamic text book. The most rapid development Muslimat NU-Fatayat marked by: "return to khitah 1926" and Lombok General Assembly 1997 which let them out of practical politics. In addition, the development of Moslem organization backed by edict-Fatayat Lombok 1997, which resulted in the "position of women in Islam" or al-mar'ah fi al-Islam that Islam recognizes equal rights between man and woman  in the realm of religious order vance.   Abstrak: Pergerakan Perempuan Islam Indonesia: Studi Tentang Fatayat Muslimat NU 1938-2013. Artikel ini bertujuan untuk meneliti dinamika pergerakan Muslimat-Fatayat NU selama periode 1938-2013 dilihat dari pendekatan sosial historis. Pergerakan perempuan Muslim Indonesia  ada  tidak hanya melalui pergerakan tahrîr al-mar‘ah, tapi juga dampak dari perkembangan pergerakan perempuan Muslim di dunia Barat. Perkembangan Muslimat-Fatayat memegang peranan penting dalam  upaya transformasi sosial. Transformasi dilakukan melalui proses kesadaran melalui “cara evolusi”, bukan radikal yang mengharuskan aktualisasi buku-buku Islam klasik. Perkembangan paling pesat dari Muslimat NU-Fatayat ditandai oleh “kembali ke  khitah 1926” dan Majelis Umum Lombok 1997 yang membawa mereka keluar dari praktik politik. Sebagai tambahan, perkembangan organisasi Muslim telah kembali dengan adanya dekrit-fatayat Lombok 1997, yang menghasilkan “posisi perempuan dalam Islam” atau al-mar‘ah fi al-Islâm bahwa Islam mengakui hak antara laki-laki dan perempuan dalam bidang agama sama. Keywords: Indonesia, perempuan Muslim, NU, Fatayat Muslimat NU